Hepatitis E-associated encephalopathy in a renal transplant recipient. (30th April 2014) - de Vries, Marijke A; Samijn, Johnny P A; de Man, Rob; Boots, Johannes M M
Abstract : Hepatitis E virus genotype 3 is not rare in developed countries, and may cause chronic hepatitis in immunocompromised patients. This may not only lead to abnormalities in liver test and malaise, but to severe neurological symptoms as well. In this case, chronic hepatitis E infection caused encephalopathy, an atactic gait, Lhermitte's sign, incomplete bladder emptying and peripheral sensory neuropathy in a renal transplant recipient. The diagnosis was not performed until years after the onset of first symptoms and several months after the onset of neurological symptoms. If treated adequately, viral load can be reduced in over two-thirds of patients and neurological symptoms are often resolved. More widespread knowledge about this virus and its extrahepatic manifestations may lead to a quicker diagnosis, and may limit pathology. Serological screening should be added to standard pretransplant virological screening, so that, in the future, patients without antibodies could be vaccinated.